Azine-bridged binuclear metallophthalocyanines functioning photophysical and photochemical-responsive - (:unkn) unknown (ELSEVIER SCI LTD, 2012)
The new phthalodinitrile containing azine-bridged (3) was prepared by the reaction of 4-nitrophthalonitrile (2) and 4,4'-(1E,1'E)-hydrazine-1,2-diylidenebis(methan-1-yl-1-ylidene)diphenol (1). The new binuclear asymmetric type zinc(II) (5), oxotitanium(IV) (6), tin(II) (7), cobalt(II) (8), copper(II) (9) and nickel(II) (10) phthalocyanine complexes containing azine moiety were synthesized by the cyclotetramerization of azine containing phthalonitrile (3) and unsubstituted phthalonitrile (4). The aggregation behaviors of these compounds were investigated at different concentrations in dimethylsulfoxide (DMSO). Furthermore, the photophysical (fluorescence quantum yields and lifetimes) and photochemical properties (singlet oxygen and photodegradation quantum yields) were studied for zinc(II) (5), oxotitanium(IV) (6) and tin(II) (7) phthalocyanine complexes in DMSO. The synthesized cobalt (8), copper (9) and nickel (10) phthalocyanine complexes were not evaluated for this purpose due to transition metal and paramagnetic behavior of central metals in the phthalocyanine cavity. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Dimeric; Azine; Fluorescence; Photophysics; Photochemistry; MICROWAVE-ASSISTED SYNTHESIS; STRUCTURAL-CHARACTERIZATION; METAL-FREE; PHTHALOCYANINES; SUBSTITUENTS; AGGREGATION; DERIVATIVES; STABILITY; LIGANDS; SOLVENT